2013
DOI: 10.1080/1331677x.2013.11517643
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implications of Insufficient Health Literacy

Abstract: The main goal of this paper is to elaborate the importance of health literacy in cost-effective utilization of health care services which influence the efficiency of the entire health care sector. In order to complement the theoretical framework of the economic implications and the circular influence of health literacy on the economy, an empirical analysis was carried out using S-TOFHLA. The results suggest that the patients' personal characteristics and the accessibility to health care services influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In Europe, a study on HL in eight EU countries [ 4 ] showed that people with low HL have a higher prevalence of long-term conditions, which in turn are more likely to be limiting, and that low HL level is significantly associated with worse self-assessed health. Research on HL in Croatia is still in its infancy, with no studies published at the national level [ 5 ] and previous published studies either using a nonvalidated instrument [ 6 ] or focusing mostly on readability, comprehension or informed consent issues [ 5 , 7 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, a study on HL in eight EU countries [ 4 ] showed that people with low HL have a higher prevalence of long-term conditions, which in turn are more likely to be limiting, and that low HL level is significantly associated with worse self-assessed health. Research on HL in Croatia is still in its infancy, with no studies published at the national level [ 5 ] and previous published studies either using a nonvalidated instrument [ 6 ] or focusing mostly on readability, comprehension or informed consent issues [ 5 , 7 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human capital is also essential in the presence of stunting and TFP growth correlation. This is because a better human capital, shown by higher enrollment rate, might associate to the better insight about health literacy and the importance of health itself (Dukic et al, 2013). The finding is shown in the Figure 4.…”
Section: Findings and Discussionmentioning
confidence: 80%
“…Thus, future research efforts of scientists should be focused on patients' confidence in a relation with their level of health literacy. This topic is receiving more and more attention and should be further developed in the issues presented by this study (Sorensen et al, 2013;Nutbeam, 2017;Dukic et al, 2013;Rolová, 2020).…”
Section: Discussionmentioning
confidence: 99%